Strategi Preventif Penyakit Tidak Menular Melalui Edukasi dan Skrining Obesitas Dewasa Muda Jakarta Barat - David Limanan; Susy Olivia (Lembaga Pengembangan Kinerja Dosen, 2025)
Obesity, central obesity, and hypercholesterolemia are prevalent yet often unrecognized health conditions that significantly elevate the risk for various non-communicable diseases (NCDs) such as diabetes mellitus, hypertension, and cardiovascular disorders. These conditions, when left undiagnosed and untreated, contribute to the growing public health burden worldwide. This community service program was designed to raise awareness and provide early detection of these conditions through basic health screening measures, including body mass index (BMI), waist circumference, and blood cholesterol levels. The program was implemented in Tomang Subdistrict, West Jakarta, where 90 participants were involved. The findings from the screening revealed concerning results: 67% of the participants were classified as obese, and 58% had central obesity, both of which are major risk factors for NCDs. A deeper analysis of lifestyle factors highlighted that high-fat diets, sedentary behaviors, and night shift work were significant contributors to the high rates of obesity and metabolic abnormalities observed. The educational outreach component of the program, which included the provision of information about healthy diets, exercise, and the importance of regular health screenings, proved to be effective in raising awareness about these health issues. Moreover, the simple health screening process was well-received by the community and contributed to a greater understanding of individual health risks. This initiative is expected to serve as a sustainable model for promoting health and preventing metabolic diseases in the community. The findings underscore the importance of early detection and education as critical strategies in the fight against obesity and related NCDs, suggesting that such programs can play a key role in reducing the future burden of chronic diseases in underserved populations